PENGARUH FUNDAMENTAL MAKROEKONOMI TERHADAP PENANAMAN MODAL ASING DI ASEAN - Kristianto, Andriyan; Zuhroh, Idah; Anindyntha, Firdha Aksari (Media Ekonomi, 2024)
This study aims to see the effect of macroeconomics fundamental that proxied by economic growth, inflation and interest rates on foreign   investment in ASEAN 5. This research uses panel data regression analysis. The data source is  from World Bank that are consist of Foreign Direct Investment, Gross Domestic Product, inflation, and   interest from 2007 to 2022. The results show that the Gross Domestic Product has a positive effect on Foreign Direct Investment. Meanwhile, the inflation and interest rates have a negative effect on Foreign Direct Investment